Comparación de la dosis estimada en recto y vejiga con planificación de Braquiterapia 3D vs 2D: Estimated dose comparison in the rectum and bladder with 3D vs. 2D brachytherapy planning (La U Investiga, 2017)
Cervical cancer is one of the main female neoplasia the treatment requires multidisciplinary management.Intracavity brachytherapy occupies a fundamental role. Brachytherapy represented an important improvement in the last years with the growth of the three-dimensional planning. But in many countries, two dimensional planning is still the only option of treatment. We seek to establish the benefit that is obtained with brachytherapy in three dimensions, in the protection to organs of risk. This is an observational, longitudinal cohort study; we extrapolated treatment schemes in three dimensions, to planning in two dimensions. Then turned to move this planning, to the tridimensional system again and we got doses- olume histograms of rectum and bladder. Finally, we determined the average of doses received in 2cc of rectum and bladder in three-dimensional planning and compared with those obtained in the two dimensional planning, using Student’s T test. The dose average in 2cc bladder in two-dimensional plan was 5.5 Gy. And in three-dimensional plan was 5.1 Gy (p=0.01). The dose average in 2cc rectum in two-dimensional plan was 2.8 Gy, and in three-dimensional plan was 3.0 Gy (p=0.06). This study gives an approximation to the dosimetry improvement obtained through the using of the three- dimensional planning, for the reduction of doses in the bladder.
Keywords: Brachytherapy; Intracavity radiotherapy; organs at risk; dosimetry; planning